Computational drug ZINPIP-Analog an ultimate solution to cure conserved domains of mutant EGFR, ALK and BRAF Proteins in NSCLC - Munir, Anum; Khan, Sajid; Azam, Shumaila (International Current Pharmaceutical Journal, 2015)
Mutations in different genes such as EGFR, ALK and BRAF results in non-small cell Lung cancer (NSCLC). The most ordinarily discovered EGFR mutations in patients with NSCLC are deletion in exon 29 or in 21. Mutations initiate the tyrosine kinase activity of EGFR and are connected with the affectability to small molecules results in the formation of NSCLC. The missense mutations of BRAF have been detected in exon 11 and 15. Mutation of ALK occurs as a result of small inversion. The primary objective of study was to design novel chemical compound to block the targeted sites for receptor proteins, present on cells surface which control the growth or stop the proliferation of cancer cells. After screening large amount of data we have designed Novel Insillico drug compound Zinpip analog for NSCLC that blocks the EGFR, ALK, and BRAF. In docked complexes ALA, LYS, and ARG were common interacting residues for EGFR and ALK. ALA and GLY were common for ALK and BRAF mutant protein and Ligand complex interaction. ALA was common among all interactions. Molecular formula of Zinpip analog completely satisfies the Lipinski rules of five. It shows less side effects and long resistance against for non-small cell lung cancer. We conclude that our drug Zinpip analog is superior to commercial drugs available in market. As it is non-toxic in nature and has no side effects. International Current Pharmaceutical Journal, June 2015, 4(7): 396-401